Yttria stabilized zirconia membrane stability in molten fluoride fluxes for low-carbon magnesium production by the SOM process - Milshtein J.; Gratz E.; Pati S.; Powell A.C.; Pal U. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The Solid Oxide Membrane (SOM) process for magnesium production involves the direct electrolysis of magnesium oxide for energy efficient and low-carbon magnesium production. In the SOM process, magnesium oxide is dissolved in a molten oxy-fluoride flux. An oxygen-ion-conducting SOM tube, made from yttria stabilized zirconia (YSZ), is submerged in the flux. The operating life of the electrolytic cell can be improved by understanding degradation processes in the YSZ, and one way the YSZ degrades is by yttria diffusion out of the YSZ. By adding small amounts of YF3 to the flux, yttria diffusion can be controlled. The diffusion of yttria into the flux was quantified by determining the yttria concentration profile as a function of immersion time in the flux and distance from the flux-YSZ interface. Yttria concentrations were determined using x-ray spectroscopy. The diffusion process was modeled using a numerical approach with an analytic solution to Fick’s second law. These modeling and experimental methods allowed for the determination of the optimum YF3 concentration in the flux to minimize yttria diffusion and improve membrane stability. Furthermore, the effects of common impurities in magnesium ores, such as calcium oxide, silica, and sodium oxide/sodium peroxide, on YSZ stability are being investigated.